GC-MS Analysis for Saturated Hydrocarbons from Jasmine (Jasminumsambac L.) Leaves Damaged by Jasmine Leaf Webworm, NusinoegeometralisGuenee (Global Journal of Science Frontier Research, 2018)
The hexane extracts of Jasminum sambac L. leaves damaged by jasmine leaf webworm, Nausinoe geometralis (Guenee) and also healthy jasmine laeves were subjected to Gas Chromatography-Mass spectrometry (GC-MS) to determine the saturated hydrocarbons. The results revealed that both the healthy and damaged leaves had hydrocarbon compounds numbering 21 and 27 respectively. The variation in the hydrocarbon profile of healthy and damaged leaves might be related to the quality of semiochemicals these plants emit, which is important for the attraction of natural enemies in jasmine ecosystem so as to reduce further infestation by budworm. In the healthy jasmine leaves, the hydrocarbons, hentriacontane and tetracosane were detected at 25.89 mins exhibiting the largest peak area of 24610830 mm2 octacosane, tetracosane, eicosane, nonacosane and heptacosane followed the order and emitted in enormous quantities. The natural enemy attractant, methyl salicylate and allylisovalerate was also detected in healthy jasmine leaves. With regard to jasmine leaf web worm infested leaves, allylisothiocyanate, allylisovalerate, divinyl sulfide, oxalic acid potential candidates for attracting natural enemies were detected in along with an array of saturated hydrocarbons.Bis (2-ethylhexyl) phthalate, a six carbon compound was detected in maximum quantity detected with the largest peak area of 144295751 mm2 at 38.984 mts in web worm damaged leaves.The quality and quanity of these semiochemicals emitted by the leaves might be the reason for attraction of natural enemies in the jasmine ecosystem there by further reducing the infestation of leaf webworm, as well as other pests. This feature can be exploited to enhance the efficacy of natural enemies in integrated management of jasmine pests.
Keywords: semiochemicals; synamones; saturated hydrocarbons; nausinoe geometralis; GC-MS; jasmine